Water Harvesting Performance of Modified Nanostructure Aluminum Using Silica Nanoparticles Coating and Laser Processing - Milin Lekmuenwai; Piyachit Yingkiatinon; Warin Namkotr; Chatchawan Tancharoensup; Tanyakorn Muangnapoh; Tippawan Sodsai; Paiboon Sreearunothai; Krissada Surawathanawises; Bhawat Traipattanakul (Nanomaterials)
Dew collection is one of the most efficient water harvesting methods. In this work, we experimentally investigated the effects of modified nanostructured surfaces on water harvesting performance. Aluminum surfaces exhibiting hydrophobic, superhydrophobic, hydrophilic, and biphilic properties were utilized in this study. The superhydrophobic surface was fabricated using a fluorinated modified silica nanoparticles coating, while nanolaser processing and the surface abrasion with sandpapers were employed to create two distinct hydrophilic structures. In addition, various biphilic surface patterns, incorporating both superhydrophobic and hydrophilic characteristics, were also fabricated. The nanolaser-treated surface demonstrated the highest water harvesting performance, achieving a water collection of 386.7 mL/m2. This performance represented a 42% increase compared to unpolished sample and a 282% increase relative to the superhydrophobic sample. Furthermore, the results indicated that the optimal biphilic surface pattern occurred at a 1:4 superhydrophobic-to-hydrophilic area ratio. The experimental outcomes were further interpreted through the mechanisms underlying water harvesting. Additionally, the experimental results were explained with the water harvesting mechanism.